Meningkatkan Pemahaman dan Budaya Literasi Terhadap Informasi Publik: Pengaruh UU ITE dan Pemanfaatan Teknologi Informasi dalam Pendidikan - Odang Hermanto (Jurnal Pengabdian Literasi Digital Indonesia, 2023)
In this digital era, it is crucial for society to possess a profound understanding of information literacy and the wise use of social media. This journal discusses how comprehension and cultural literacy regarding public information can be enhanced, considering the limitations imposed by the Information and Electronic Transactions Law (UU ITE) on social media. Furthermore, this journal also explores how information technology can be harnessed as a means to enhance education. In the current digital age, public information has become more accessible through social media and other online platforms. However, the presence of the Information and Electronic Transactions Law (UU ITE) gives rise to constraints on the use of social media. This paper deliberates efforts to amplify comprehension and cultural literacy concerning public information and examines how the utilization of information technology can support education in facing the constraints regulated by the UU ITE. With a focus on social media usage and the implications of the UU ITE, as well as the utilization of information technology in education, this research aims to identify endeavors to augment the understanding of accurate and relevant information amidst the complexity of digital information